Implementasi Konsep Kesantunan Budaya Jawa pada Seni Pertunjukan Langendriya Mandraswara Mangkunegaran - Sutarno Haryono (Greget, 2009)
When Mangkunegara IV was in power in the Mangkunegaran (1853-1881), he created several new art forms, one of which was Langendriya Mandraswara, which uses as its media both verbal and non-verbal components. The verbal component, traditional Javanese singing, or tembang macapat, is adapted to suit the social strata and takes into consideration the principle of politeness. The non-verbal component expresses a particular character. The integration of the two components creates a clearer, more communicative, and more aesthetic meaning.Keywords: Politeness, verbal and non-verbal components